Rethinking Liberal Democracy in Nigeria’s Post-Colonial Democracy - Okutalukwe , Chidiebere; Igoli, Timipa (Kashere Journal of Politics and International Relations, 2023)
This paper focuses on the unpacking of liberal democratic policies that are characterized on the logic of election and methodical individualism in the post-colonial Nigeria. This characterization is chiefly driven by the post-colonial authoritarian nature of policies underpinned by exclusion and deprivation that signpost Nigerian state and her evolving democratic space. Liberal democracy is an Eurocentric metropolitan type of democracy that reinforces elitism, disempowerment and negates the principle of popular consciousness built around subaltern political emancipation. The study therefore, interrogates the role of election in strengthening the epistemic value of democracy. The Nigerian state still manifest the legacies of colonial empire rationality in shaping her democratic institutions, practices and norms that are devoid of “spivakian” postcolonial discourse that centers around incursion, empowerment, reciprocity and solidarity. This reifies binary opposition of rulers and the ruled in consolidating democratic culture in Nigeria. The study engages qualitative data as its main methodological guide. The study discovers that rethinking the liberal democratic politics in Nigeria through subaltern discourse will provoke an intellectual engagement that will lead to the emergence of deliberative democracy.